STRATEGI KOMUNIKASI CORPORATE COMMUNICATION PT. RIAU ANDALAN PULP AND PAPER DALAM MENSOSIALISASIKAN PRINSIP 5C MELALUI MEDIA SOSIAL TWITTER - Karina Satriana Putri; Muhammad Firdaus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Social media has been in great demand by various agencies and companies both large and small today. Utilization of social media is also carried out by large multi-national companies such as PT. Riau Andalan Pulp and Paper (RAPP), a company which defecate in industrial environments, RAPP susceptible oblique issues about policy and the environment. RAPP but in fact operates on the principle of 5C initiated by Tanoto as the founder of RAPP that are: Good for the Community, Good for the Country, Good for Climate, Good for the Customer and Good for the Company. Corporate communication as the main communication lines of the company has its own communication strategy in socializing the 5C principles that run the company through social media twitter.The purpose of this research is to find out the communicator strategy, the message strategy and the driving and inhibiting factors of Riau Andalan Pulp and Paper corporate communication strategy in socializing 5C principal through social media twitter.This study used qualitative research methods. Informants in this study is 6 (six) staff corporate communication including social media ambassadors using determined purposive sampling. The data collection technique is through interview, observation and documentation. Data analysis used in this research is Huberman and Miles model. To achieve the validity of the data, in this study researchers used a triangulation technique.The results showed that the communication strategy used is the strategy aspect of communicator, message strategy and there are also factors driving and inhibiting factors. Communicator strategy is staff corporate communication particularly digital media team as the main communicator and social media ambassador for the company. Strategic corporate communications message composing a message with a specific composition, timing and type of messages that will be shared. The message type is divided into two, namely the message informative and persuasive messages. As for the driving and inhibiting factors, from there driving factors of internal factors. For inhibiting factors obtained from internal and external factors.Keyword: Corporate Communication,Communication Strategy, RAPP 5C Principle, twitter